2019
DOI: 10.1142/s0192415x19500228
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Suppresses RANKL-Induced Osteoclast Differentiation by Inhibiting c-Fos and NFATc1 Expression

Abstract: Osteoporosis is a common disorder of bone remodeling, marked by excessive osteoclast formation. Recent studies indicated that berberine (BBR) is a potential natural drug for the treatment of various bone diseases. However, it still needs to be further studied for the treatment of osteoporosis. The current study investigated the inhibitory effects of BBR on receptor activator of nuclear factor-[Formula: see text]B ligand (RANKL)-induced osteoclast differentiation in vitro and in vivo. Cell-based assays were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…OSCAR is specifically expressed in early stage osteoclasts or in mature osteoclasts, and induces calcium activation to assist in the expression of RANKL-mediated NFATc1 (54). Similar to these results, the majority of osteoclast inhibition studies have reported that osteoclast-related genes are decreased by reduction of c-Fos and NFATc1 (55,56). OC-STAMP and ATP6v0d2 are expressed when the osteoclast precursor cells are fused, and when it is deficient, differentiation into osteoclasts is not completed.…”
Section: Discussionsupporting
confidence: 81%
“…OSCAR is specifically expressed in early stage osteoclasts or in mature osteoclasts, and induces calcium activation to assist in the expression of RANKL-mediated NFATc1 (54). Similar to these results, the majority of osteoclast inhibition studies have reported that osteoclast-related genes are decreased by reduction of c-Fos and NFATc1 (55,56). OC-STAMP and ATP6v0d2 are expressed when the osteoclast precursor cells are fused, and when it is deficient, differentiation into osteoclasts is not completed.…”
Section: Discussionsupporting
confidence: 81%
“…There are two pathways for osteoclast proliferation, differentiation, and maturation, 38 and the main pathway is the RANKL/RANK/OPG system, which has been expressed in the early stage of OP. 39 The secondary pathway is the pathway of inflammatory factors. 40 RANKL is the only factor currently found to induce osteoclast differentiation, development, and function.…”
Section: Discussionmentioning
confidence: 99%
“…It’s well known that microRNAs can inhibit the expression of target genes by binding to complementary segments of messenger RNA and interfering with the formation of proteins by translation. 39 Previous studies have found that miR-93-5p and miR-378 were involved in the regulation of OP by binding to BMP-2, a number of active bone morphogenetic proteins. 46 , 47 Therefore, BMP-2 may play a critical role in miRNA-mediated regulation of OP.…”
Section: Discussionmentioning
confidence: 99%
“…For the ACS, an acute and severe cardiovascular disease, the medical treatment is difficult, its mortality is high, and its clinical manifestation and prognosis are very various, so early judgement for ACS prognosis is very important for the patients with ACS. The human OSCAR, a cell surface molecule, is involved in osteoclast differentiation and bone metabolism 6 . OSCAR may play an important role in vascular inflammation or plaque vulnerability during atherosclerosis 7 .…”
Section: Discussionmentioning
confidence: 99%